2021
DOI: 10.1016/j.heliyon.2021.e06712
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital and financial performance of South African development community’s general insurance companies

Abstract: The effect of intellectual capital on financial performance was investigated in this paper for the period 2008 to 2019. A total of 696 observations were generated from data collected from 56 general insurance companies in 12 years. The Value Added Intelligent Coefficient Model was used and data was analysed using both static (two stage least square, fixed and random effect) and dynamic panel regression analysis (two step system generalised method of moments). The findings showed a significant and direct relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 69 publications
1
21
0
13
Order By: Relevance
“…As a result, the Insurance Regulatory Authority was established, which is a governmental agency that regulates, promotes, and oversees SADC's insurance sector. Notably, insurance firms' earnings have been declining in recent years (Olarewaju & Msomi, 2021). In addition, the influence of firm characteristics on firm performance is adequately supported by past research.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…As a result, the Insurance Regulatory Authority was established, which is a governmental agency that regulates, promotes, and oversees SADC's insurance sector. Notably, insurance firms' earnings have been declining in recent years (Olarewaju & Msomi, 2021). In addition, the influence of firm characteristics on firm performance is adequately supported by past research.…”
Section: Introductionmentioning
confidence: 74%
“…These necessitate the importance of examining the firm's characteristics (such as equity capital, company age, company size, underwriting risk, operational efficiency, claim ratio, leverage ratio, liquidity ratio, and investment capabilities), as well as firm's financial performance. In SADC, the dearth of a regulating authority has culminated in the insurance industry's poor performance over the last couple of years, with many companies closing due to a lack of capital (Olarewaju & Msomi, 2021). As a result, the Insurance Regulatory Authority was established, which is a governmental agency that regulates, promotes, and oversees SADC's insurance sector.…”
Section: Introductionmentioning
confidence: 99%
“…Çünkü dünyanın dört bir yanındaki piyasalar, sermaye yoğun olmaktan bilgi yoğun olmaya doğru endüstriyel bir değişim içindedir (Nawaz ve Haniffa, 2017;Ozkan vd., 2017). Bu bağlamda maddi olmayan bir varlık olarak entelektüel sermaye, artık böyle bir piyasa ortamında büyümeyi ve rekabeti teşvik eden ana faktörlerden biri olarak karşımıza çıkmaktadır (Olarewaju ve Msomi, 2021). Bu nedenle işletmelerin tüm değerli entelektüel sermayelerini bir araya getirerek, bunları önceden belirledikleri stratejik hedefler doğrultusunda kullanmaları işletmelere değer katarak onların kazançlarını arttıracaktır (Oppong vd., 2019).…”
Section: Introductionunclassified
“…İkincisi, bilindiği kadarıyla Türkiye' de sigortacılık sektöründe yapılan benzer çalışmaların sadece Borsa İstanbul' da işlem gören sigorta şirketlerini kapsaması (Aktaş, 2015;Bölükbaşı, 2014) ve bu çalışmaların sınırlı sayıda olmasıdır. Üçüncüsü ise entelektüel sermaye etkinliğinin, sigorta şirketlerinin performansı üzerindeki etkisinin birçok gelişmekte olan ülkede araştırılıyor olması (Lu vd., 2014;Olarewaju ve Msomi, 2021;Oppong vd., 2019) ve bu nedenle Türkiye sigorta şirketleri için de bu konunun araştırılma gereğinin ortaya çıkmasıdır. Tüm bu nedenler doğrultusunda, yapılan bu çalışmayla birlikte elde edilen bulguların, sigorta şirketlerine, araştırmacılara, düzenleyici kurumlara ve mevcut literatüre önemli katkılar sağlayacağı düşünülmektedir.…”
Section: Introductionunclassified
“…shown that intangible assets have a positive effect on company performance (Olarewaju and Msomi, 2021;Del Monte and Papagni, 2003;Zhu and Huang, 2012). More recent researches (Xu and Wang, 2018;Ocak and Fındık, 2019) focused on the impact of IC and intangibles on the companies' sustainable growth rate and performance.…”
Section: Introductionmentioning
confidence: 99%